"A plague of wild boars": A New History of Pigs and People in Late 20th Century Europe. Issue 4 (24th February 2016) - Fleischman, Thomas
Abstract: This paper looks at an ungulate irruption of wild boars that occurred in the German Democratic Republic (GDR) in the 1970s and 1980s. It argues that this hybrid phenomenon resulted from the confluence of three historically specific, intertwined factors in late 20th century Europe: first, East Germany's embrace of development ideology to remake their farms and forests; second, the simultaneous introduction of a specifically East German conservation program; and third, a new era in the longue durée of human–pig relationships. This ungulate irruption was particular to the GDR and the central European landscape of the Cold War, and only becomes visible through careful attention to the historical context and the materiality of pigs ( Sus scrofa ). For this reason it is possible to call these pigs new creatures of development. More broadly this paper asks both historians and social scientists to account for the temporal and spatial context when analyzing hybrid phenomena, while also raising important questions about the meaning and application of the neologism Anthropocene.